Pengaruh Pengetahuan Peraturan, Komitmen Manajemen, Dan Lingkungan Birokrasi Terhadap Penyerapan Anggaran Terkait Pengadaan Barang/Jasa - Muhammad Ikhsan; Vita Fitria Sari (Universitas Negeri Padang, 2020)
This study aims to determine the effect of regulatory knowledge, management commitment, and the bureaucratic environment on budget absorption related to the procurement of goods / services in the government of Padang City. A sample of 82 respondents was determined by using a total sampling technique consisting of heads of fields or staff of the procurement department. Data were analyzed using multiple regression formulas with the help of the SPSS application. This study concludes that regulatory knowledge does not affect budget absorption related to goods / services procurement. Management commitment has a positive and significant effect on budget absorption related to the procurement of goods / services. Meanwhile, the bureaucratic environment has no effect on budget absorption related to the procurement of goods / services